(untitled) (Journal of Geography and Environmental Management, 2019)
The questions of methodic of calculation of intra annual water fl ow distribution of the main rivers of Ertis water basin right bank were investigated. There was conducted a comparative analysis of the obtained results for the last thirty four years and the results shown in “The resources of the USSR surface waters” in the area of research, and also the results obtained in a period with conditionally-natural water fl ow (1933-73). There was shown the data about changes in seasonal fl ow distribution that happened in the last thirty four years.